(untitled) (diségno, 2018)
The recurring references to the topic of measurement in perspective studies between the seventeenth and eighteenth centuries highlight a return to objectivity in the method of perspective representation at a time when more emphasis was placed on its perceptive aspect. The present contribution examines a series of treatises, which contributed to achieving the perspective construction system of the measuring points, together with the evolution of a number of instruments used to measure architectural structures and spaces. The manuscript on perspective by Jacques Alleaume, written in 1627 and posthumously published by the mathematician Estienne Migon (La perspective speculative et pratique, 1643), contains one of the first methods to represent segments in perspective, which are assigned by values of inclination and length. The identification of the measuring points through the progressive generalisation of the problem is first found in the Cours de mathém- atiques by Jacques Ozanam (1693) and then in the work by Brook Taylor (Linear Perspective, 1715), whose most noted contribution was the systematisation of the reverse perspective method. The claim by Ozanam to extend the use of the Universal Instrument to practical geometry (1688) reflects the general focus on the topic of measurement with regard to the fundamentals in theoretical mathematics, the scientific value of the representation methods, and the instruments to survey architectural structures.